The Development of Adobe Flash to Learning Dayak Traditional Music for Students in Junior High School - Sartika Dewintha; Aloysius Mering; Indri Astuti (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to describe the design of the development, appearance, and process of Adobe Flash learning outcomes for learning traditional Dayak music for junior high schools. In this study involved media experts, material experts, design experts, fellow teachers, small, medium and large group trials. The subject of the trial was the eighth-grade students of Pontianak Public Middle School 10. Data obtained through interviews, observation and documentation studies. This study uses Research & Development research. The results of this study will later produce a product. Development research carried out combines the steps of Borg & Gall's development with the Dick and Carey model. The results showed that the media used was appropriate to be used as a learning medium for traditional Dayak music. The average level of feasibility based on the validator is that media experts have "feasible" eligibility criteria, "decent" material experts and "decent" design experts. Based on the results of the small group test scores "quite feasible," the trial group was "decent" and a large group test "feasible."